Students' Opinions Regarding the Use of Online Didactic Support in a University Course - Javier Organista Sandoval; Eduardo Backhoff Escudero (Universidad Autónoma de Baja California, 2002)
In Mexico recently a variety of online teaching support has begun to be used for giving higher-education courses. However, little is known about students' perceptions of this matter. The purpose of this work was to find out the opinions of the university students who took a computer-aided course that used the Internet for turning in assignments, taking exams and receiving tutorial advice. The differences of opinion were analyzed, considering socioeconomic variables, and variables of academic performance. The results indicate that the students favor the use of this kind of educational support, and that there were no important differences of opinion.